ANALYSIS OF SEPARATOR-CLEANER TRANSMISSIONS (Scientific journal of the Fergana State University, 2025)
The article analyzes the classification, operating principle and efficiency of a new separator-cleaner that allows the separation of cotton from the air and its cleaning, as well as the transmission mechanisms that drive it, the separator-cleaner has a drum with piles and a mesh surface arranged symmetrically in a vertical plane with a vacuum valve that allows the cotton to be separated from the air and cleaned of impurities.